Characterization of the new beta-glucuronidase from Streptococcus equi subsp. zooepidemicus - Krahulec, Ján; Krahulcová, Jana (Applied microbiology and biotechnology, 2007)
Recently, a new gene encoding beta-glucuronidase from Streptococcus equi subsp. zooepidemicus (SEZ) was identified and expressed in Escherichia coli. In this paper, the characterization of the enzyme is described. Specific enzyme activity was 120,000 U/mg purified protein at 37 degrees C and pH = 7.0. The temperature and pH value, at which the enzyme has the highest specific activity, were determined and were found to be approximately 52 degrees C and 5.6, respectively. The mutant strain SEZ glcHis was designed for the efficient isolation of beta-glucuronidase from S. equi subsp. zooepidemicus. It was observed that the specific activity of beta-glucuronidase in the cytoplasmic extract of a mutated strain was about 45% lower than in the cytoplasmic extract of a wild-type strain. The specific activity of purified beta-glucuronidase from SEZ glcHis was four times as low as beta-glucuronidase purified from E. coli. Comparing the specific activity of purified streptococcal beta-glucuronidase from E. coli with E. coli beta-glucuronidase (the enzyme with the highest specific activity was supplied by Sigma), the former is 1.8 higher than the latter.
Keywords: klonování DNA; glukuronidasa; financování organizované; Financing, Organized; Cloning, Molecular; Glucuronidase; Streptococcus equi